A F-deficient and high-Mn ternary perovskite fluoride anode with a dominant conversion mechanism for advanced Li-ion batteries. Issue 62 (14th July 2021) - Huang, Yongfa; Ding, Rui; Ying, Danfeng; Huang, Yuxi; Tan, Caini; Yan, Tong; Sun, Xiujuan; Liu, Enhui
Abstract : A F-deficient and high-Mn ternary perovskite fluoride anode synthesized by a one-step solvothermal method is suitable for advanced lithium-ion batteries with a dominant conversion mechanism. Abstract : A F-deficient and high-Mn ternary perovskite fluoride anode (K1.00 Ni0.06 Co0.14 Mn0.80 F2.92, KNCMF-3#) has been explored for advanced Li-ion batteries (LIBs), showing a dominant conversion mechanism. Notably, the KNCMF-3#//LiFePO4 (LFP) LIBs furnish an ultra-high performance of 270.5–35.9 W h kg −1 /0.63–11.6 kW kg −1 /71% retention/5000 cycles/5 A g −1 .